Communicating Architectural Knowledge - Schwittek, Widura; Eicker, Stefan (Proceedings of the 4th European Conference on Software Architecture (ECSA 2010), 2010)
Architecting is a communication intensive task in which architectural knowledge is shared between the architect and the stakeholders. The software architect’s communicative action is often conducted face-to-face, e.g. in presentations and workshops. A software architecture documentation as a carrier of explicit architectural knowledge can also be seen as an architect’s communicative action. This perspective opens the door for treating a software architecture documentation as an expression of an asynchronous knowledge communication process enabling the application of principles from communication theory. In this paper this perspective is taken and specific requirements are derived for software architecture knowledge management tools with respect to the contextoriented communication model.
Keywords: software architecture; architectural knowledge; knowledge communication